Postoperative Perianal Abscess and Concomitant Anorectal Fistula: An Extremely Rare Complication After Emergency Transanal Hemorrhoidal Dearterialization With Mucopexy for Hemorrhoidal Disease - Charito Chatzinikolaou; Konstantinos Perivoliotis; Amalia Moula; Kyriakos Psarianos; Alexios Stavrou; Ioannis Baloyiannis (Case Reports in Surgery)
We report the rare case of postoperative perianal abscess after emergency transanal hemorrhoidal dearterialization (THD) with mucopexy for Grade III hemorrhoidal disease (HD). A 68-year-old male presented to our hospital with rectal bleeding due to HD Grade III. He underwent THD with mucopexy with an uneventful postoperative recovery. The patient was evaluated on the 15th postoperative day due to perianal pain without any abnormal laboratory and imaging findings. One month postoperatively he presented with perianal edema and pus discharge. During the rectal examination, a perianal abscess with a concomitant fistula was identified and was confirmed with an MRI scan. He was submitted to abscess drainage and seton placement. This report aims to raise awareness among colorectal surgeons about the risk for this specific complication during the postoperative period. Further studies, are needed so that the etiopathology of this condition is identified and the risk factors can be controlled and avoided.